Analysis of Profit Management in Agricultural Companies in the Plantation Sub Sector Listed on the Indonesia Stock Exchange, Through PPH Rates and Tax Planning - Putri Wahyuni; Muammar Rinaldi (Outline Journal of Management and Accounting, 2023)
This study aims to determine whether the corporate income tax rate and tax planning have a significant effect on earnings management in agricultural companies in the plantation sub-sector listed on the Indonesia Stock Exchange. The population in this study are plantation sub-sector companies listed on the Indonesia Stock Exchange as many as 19 companies. The research sample was 6 companies with purposive sampling technique. The results showed that corporate income tax rates had no significant effect on earnings management in plantation sub-sector companies listed on the Indonesia Stock Exchange, while tax planning had a significant effect on earnings management in plantation sub-sector companies listed on the Indonesia stock exchange. The results of the F test show that the variables of Corporate Income Tax Rate and Tax Planning have a significant effect on Earning Management in plantation sub-sector companies listed on the Indonesia Stock Exchange. The results of the coefficient of determination test indicate that the Earnings Management variable can be explained by the Corporate Income Tax Tariff and Tax Planning variables, while the remaining Earnings Management variables can be explained by other variables not examined in this study such as Leverage and Financial Performance.